2018
DOI: 10.1007/s11769-018-0959-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Biogenic Elements in Phragmites australis and Suaeda salsa from Salt Marshes in Yellow River Delta, China

Abstract: Little information is available on biogenic elements (carbon, nitrogen, phosphorus and sulfur) and the ecological stoichiometric characteristics of plants in coastal wetlands. To investigate the contents of carbon, nitrogen, phosphorus and sulfur of plants, and their ecological stoichiometric characteristics in the Yellow (Huanghe) River Delta, plant samples were collected from two typical salt marshes (Suaeda salsa and Phragmites australis wetlands) during the period of from August to October in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…2), which was far lower than that in C 3 -dominated coastal marshes in San Francisco Bay estuary (1-17‰) (Cloern et al, 2002). The wetland ecosystems in the YRD, like many northern and temperature forests, are nitrogen-limited (Reay et al, 2008;Jia et al, 2018). N limitation might influence nitrogen availability of wetland plants and thus accumulation process of soil δ 15 N (King et al, 2009;McLauchlan et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…2), which was far lower than that in C 3 -dominated coastal marshes in San Francisco Bay estuary (1-17‰) (Cloern et al, 2002). The wetland ecosystems in the YRD, like many northern and temperature forests, are nitrogen-limited (Reay et al, 2008;Jia et al, 2018). N limitation might influence nitrogen availability of wetland plants and thus accumulation process of soil δ 15 N (King et al, 2009;McLauchlan et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…reported that the recalcitrant compounds (such as cellulose and lignin) in litter displayed negative correlation with litter decomposition. The cellulose and lignin contents in litter of T. chinensis were higher than those in litter of herbs, resulting in lower decomposition rate . Mou et al .…”
Section: Discussionmentioning
confidence: 98%
“…In the herb layer, the TC content was almost constant among different parts and communities in the supratidal zone, but herbs in the supratidal zone accumulated more C than those in the intertidal zone (Figure a), as the TC content in the intertidal vegetation (e.g., S. salsa ) was lower compared to the supratidal vegetation (e.g., A. capillaris and S. viridis ) . In addition, the TN content was allocated more in the aboveground parts and varied among different communities and survival conditions (Figures and , and Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pall. communities in degraded saline lands ( Sui et al., 2013 ), but the mechanism responsible for betacyanin change remains unclear ( Jia et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%